PENERAPAN METODE KARYA WISATA UNTUK MENINGKATKAN HASIL BELAJAR DAN AKTIVITAS SISWA PADA PEMBELAJARAN BIOLOGI - Munawar Malik; Chumidach Roini; Arini Zohratun Nashicah (UNIVERSITAS KHAIRUN, 2022)
This study aims to improve student learning outcomes and activities at MTs Miftahul Jannah Desa Dedeta through the application of the field trip method with Biology material. This research is a classroom action research (PTK). The sequence of activities carried out in this study included: (1) planning (2) implementation (3) observation and (4) reflection, where the subjects in this study were students of class VII MTs Miftahul Jannah, Desa Dedeta and the instruments used in this study were with multiple choice test, which consists of 10 questions. Based on the results of data analysis, it shows that there is an increase in learning outcomes and student activities on the concept of classification of living things through the application of the field trip method in class VII MTs Miftahul Jannah, Desa Dedeta for the 2020/2021 academic year. In the first cycle there were 10 students who completed or 59% with a mean value of 63.53. Cycle II there was an increase with an average score of 73.53 of the students' completeness, namely 15 students who completed. The percentage of student activity in the first cycle at the first meeting had a value of 55.56% with the less activity category and at the second meeting it was 61.11 with the enough activity category. In the second cycle the value obtained was 72.22% with the enough activity category and at the second meeting was 88.89% in the very good category with learning practices using the application of the field trip method.